Optimization of high strength light-weight printable concrete - Tan, Jared Chao Yang (2018)
Printability of concrete is determined by three characteristics which are pumpability, flowability and buildability. To possess these characteristics, the aggregates need to have a gradation of particles to help flow, rough surface and angular shape to have sufficient internal resistance for buildability. Lightweight aggregates such as cenospheres on the other hand does not have a gradation. It has a smooth surface and a spherical shape. While the use of lightweight aggregates brings numerous benefits such as thermal and acoustic insulation, the pumping and buildability of lightweight aggregates especially cenospheres remains as an issue. However, addition of sand or binder may help in this aspect. Therefore, this study aims to determine the composition required in the lightweight concrete mix by using a software as well as theoretical and experimental analysis. Some of the theoretical analysis used to describe the phenomenon behind the printability of lightweight concrete are sieve analysis as well as excess paste theory. In addition to this, compressive test as well as rheology tests would be conducted to provide an accurate and optimal ratio for the respective materials required in the lightweight concrete mix.